VD_FINDINFO AP / 2009 / 30 vom 15. Oktober 2008 - VD Tribunal cantonal (2008)
VIOLENCE CONTRE LES AUTORITÉS, PEINE PÉCUNIAIRE, SURSIS À L'EXÉCUTION DE LA PEINE | 110 ch. 3 CP, 285 ch. 1 CP, 41 ch. 1 CP, 41 ch. 2 CP, 42 CP, 415 CPP